A long and abundant non-coding RNA in Lactobacillus salivarius. Issue 9 (17th July 2017) - Cousin, Fabien J.; Lynch, Denise B.; Chuat, Victoria; Bourin, Maxence J. B.; Casey, Pat G.; Dalmasso, Marion; Harris, Hugh M. B.; McCann, Angela; O'Toole, Paul W.
Abstract : Lactobacillus salivarius, found in the intestinal microbiota of humans and animals, is studied as an example of the sub-dominant intestinal commensals that may impart benefits upon their host. Strains typically harbour at least one megaplasmid that encodes functions contributing to contingency metabolism and environmental adaptation. RNA sequencing (RNA-seq)transcriptomic analysis of L. salivarius strain UCC118 identified the presence of a novel unusually abundant long non-coding RNA (lncRNA) encoded by the megaplasmid, and which represented more than 75 % of the total RNA-seq reads after depletion of rRNA species. The expression level of this 520 nt lncRNA in L. salivarius UCC118 exceeded that of the 16S rRNA, it accumulated during growth, was very stable over time and was also expressed during intestinal transit in a mouse. This lncRNA sequence is specific to the L. salivarius species; however, among 45 L. salivarius genomes analysed, not all (only 34) harboured the sequence for the lncRNA. This lncRNA was produced in 27 tested L. salivarius strains, but at strain-specific expression levels. High-level lncRNA expression correlated with high megaplasmid copy number. Transcriptome analysis of a deletion mutant lacking this lncRNA identified altered expression levels of genes in a number of pathways, but a definitive function of this new lncRNA was not identified. This lncRNA presents distinctive and unique properties, and suggests potential basic and applied scientific developments of this phenomenon.